1999
DOI: 10.1076/jcen.21.5.643.871
|View full text |Cite
|
Sign up to set email alerts
|

Mental Representation of Knowledge Following Frontal-Lobe Lesion: Dissociations on Tasks Using Scripts

Abstract: Twenty-three frontal-brain-damaged subjects, 10 posterior-brain-damaged subjects and 10 normal controls were compared on script tasks. They were first asked to re-establish the sequential and hierarchical structure of 2 script actions, and then, they were asked to order 2 new scripts which contained aberrant items. Impairments in script information processing were observed only in frontal patients. Of the 23 frontal patient tested 8 made errors in ordering actions, in choosing scenes and in making estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 47 publications
(65 reference statements)
2
22
1
5
Order By: Relevance
“…Ordination errors in our patients (M = 11; SD = 10.5) were much more frequent than those found in Allain's group of 23 patients with frontal cortical lesions (M = 2.4; SD = 3.4). The number of intrusion errors, however, was lower in our group (M = 0.5; SD = 1) when compared to the same Allain's frontal patients (M = 3.3; SD = 2.7) 18 . Lesions in different parts of the frontal lobe produce different combinations of neuropsychological symptoms, especially when comparing the orbitofrontal and dorsolateral portions 31 , which is compatible with the existence of multiple functional executive systems 32 .…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Ordination errors in our patients (M = 11; SD = 10.5) were much more frequent than those found in Allain's group of 23 patients with frontal cortical lesions (M = 2.4; SD = 3.4). The number of intrusion errors, however, was lower in our group (M = 0.5; SD = 1) when compared to the same Allain's frontal patients (M = 3.3; SD = 2.7) 18 . Lesions in different parts of the frontal lobe produce different combinations of neuropsychological symptoms, especially when comparing the orbitofrontal and dorsolateral portions 31 , which is compatible with the existence of multiple functional executive systems 32 .…”
Section: Discussionmentioning
confidence: 52%
“…Lesions in different parts of the frontal lobe produce different combinations of neuropsychological symptoms, especially when comparing the orbitofrontal and dorsolateral portions 31 , which is compatible with the existence of multiple functional executive systems 32 . For Allain 18 , the ability of performing a sequential ordination and that of eliminating irrelevant elements can represent two distinct executive processes accomplished by the frontal region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the participants were asked to place the events in a script into the correct temporal order, all but one of the prefrontal patients made errors, whereas the other groups performed without error. Other studies have found that patients with prefrontal lesions are less able than controls to identify violations of normal sequential structure in scripts and to identify events that are not part of a script (Sirigu, et al, 1996;Allain, Le Gall, Etcharry-Bouyx, Aubin, & Emile, 1999).…”
Section: Event Models and Event Schematamentioning
confidence: 99%